"Ensuring educational quality: Key strategies for accreditation agency of Higher Distance Education in Panama" (Revista Electrónica Calidad en la Educación Superior, 2024)
Evaluation consists of determining the value of an object or service with methodologies and critical judgment to identify areas for improvement. In Latin America and the Caribbean, evaluation in distance education lacks specific regulations and presents challenges in quality and accreditation. It is proposed to analyze the evaluation processes in higher distance education in the region to implement good practices that promote academic training in Panama. The study is based on a documentary review and qualitative analysis of previous perceptions and experiences. It is concluded that it is necessary to strengthen the specific regulatory frameworks for distance education and adjust criteria and standards to adequately evaluate the quality of the programs and learning results in this modality.
Keywords: education quality; : Distance education; Continuous Improvement; strategies; Standardization; Accreditation Agencies